Combined HDAC1 and HDAC2 Depletion Promotes Retinal Ganglion Cell Survival After Injury Through Reduction of p53 Target Gene Expression. (27th June 2015) - Lebrun-Julien, Frédéric; Suter, Ueli
Histones deacetylases (HDACs), besides their function as epigenetic regulators, deacetylate and critically regulate the activity of nonhistone targets. In particular, HDACs control partially the proapoptotic activity of p53 by balancing its acetylation state. HDAC inhibitors have revealed neuroprotective properties in different models, but the exact mechanisms of action remain poorly understood. We have generated a conditional knockout mouse model targeting retinal ganglion cells (RGCs) to investigate specifically the functional role of HDAC1 and HDAC2 in an acute model of optic nerve injury. Our results demonstrate that combined HDAC1 and HDAC2 ablation promotes survival of axotomized RGCs. Based on global gene expression analyses, we identified the p53-PUMA apoptosis-inducing axis to be strongly activated in axotomized mouse RGCs. Specific HDAC1/2 ablation inhibited this apoptotic pathway by impairing the crucial acetylation status of p53 and reducing PUMA expression, thereby contributing to the ensuing enhanced neuroprotection due to HDAC1/2 depletion. HDAC1/2 inhibition and the affected downstream signaling components emerge as specific targets for developing therapeutic strategies in neuroprotection.